Uji Toksisitas Ekstrak Daun Sirih (Piper betle) Terhadap Benih Ikan Kakap Putih (Lates calcarifer) - Leni Mardiana; Nunik Cokrowati; Alis Mukhlis (Rekayasa, 2022)
White snapper (Lates calcarifer) is a type of seawater fish that is in great demand by the public. This study aims to determine the 48-hour LC50 value and the effect of using betel leaf extract on the health status of white snapper. This research was conducted in July 2020 which took place at the Sekotong Coastal Aquaculture Development Center (BPBPP), West Lombok Regency, West Nusa Tenggara. This research was conducted using experimental methods. This study used 5 treatments and three replications, to obtain 15 experimental units with doses of 0 ppm, 80 ppm, 90 ppm, 100 ppm and 200 ppm. Data analysis was performed using a linear regression test, namely probit analysis by testing the mortality of tested animals and calculated through statistical data using Microsoft Excel. The higher the betel leaf extract concentration, the higher the number of white snapper seed deaths. This happens because the betel leaf extract contains active antimicrobial compounds, but at high concentrations, it can poison the white snapper seeds. For further research, it is recommended to test the toxicity of betel leaf extract on the mortality of white snapper with variations in water quality.